Determination of the risk condition for the drilling cuttings re-injection process into depleted wells in two offshore platforms at the southwest of the Campeche Sonda - García, M. Muriel (2009)
Potential risks associated with the cuttings re-injection process as an alternative method for drilling wastes disposal were identi- fied and assessed in two offshore platforms located at the southwest of the Campeche Sonda in Mexico. Risks were evaluated using the HAZOP methodology, to identifying hazards in 11 nodes. In addition, deviations in the process were analyzed, and each risk analyzed was categorized as tolerable or non-tolerable and providing some recommendations. Consequences derived from accidental spills of slurry and/or cuttings were analyzed using the mathematical model YAXUM 3D to simulate the pollu- tants dispersion in seawater in three different climatic periods. The results of the consequences analysis shows that even the concentrations in the discharge point exceeded the recommended criteria for protection of the marine life and seawater quality, the spill is rapidly dispersed complying with permitted levels in 8 hr as a maximum.